THE IMPLEMENTATION OF BEHAVIORISTIC INTERVENTIONS USING SELF-MANAGEMENT TECHNIQUES TO OVERCOME DIFFICULTIES IN TIME MANAGEMENT AND GOAL SETTING FOR HIGH SCHOOL STUDENTS PARTICIPATING IN EXTRACURRICULAR ACTIVITIES - Baroroh, Nurin; Anikoh, Indifatul; Rahman, Abd (Jurnal At-Taujih, 2025)
Time management is the ability to allocate and utilize time to achieve a balance between study activities and extracurricular activities. Difficulties in managing time are common among high school students who participate in extracurricular activities. The subject of this study is a ninth-grade student who serves as the student council president. The subject aims to balance academic achievement with the extracurricular activities they participate in. The method used in this study is a behavioral intervention employing self-management techniques combined with Time management and goal setting. The stages of the intervention are as follows: (1) Building rapport, explaining the intervention stages, and creating a learning contract for the duration of the intervention. (2) Pre-test on time management, followed by Time management materials and assignments. (3) Pre-test on goal setting using the SMART method. (4) Post-test on Time management and goal setting. The results of the intervention showed that the client was able to organize their daily schedule more easily and set daily goals using the SMART method.